1993
DOI: 10.1128/aac.37.10.2187
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of fluconazole in patients with AIDS

Abstract: Fluconazole pharmacokinetics were evaluated for 10 volunteers with AIDS who had no clinical evidence of gastroenteritis. Single 100-mg intravenous (i.v.) and oral (p.o.) doses were administered in a randomized, crossover design. i.v. doses were delivered by a constant-rate infusion over 30 min. Serum fluconazole concentrations were measured by gas-liquid chromatography. The i.v. and p.o. studies were modelled simultaneously by iterative two-stage analysis, which provided individual parameter estimates and a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
4
29
1
Order By: Relevance
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 70%
“…The mean population pharmacokinetic parameter estimates were in the same range as those already reported [14,15,16,17]. Although a previous study reported no e ect of BW on¯uconazole pharmacokinetics [16], in this study BW signi®cantly in¯uenced¯uconaz-ole CL and V d .…”
Section: Discussionsupporting
confidence: 70%
“…Since the pharmacokinetics of ddI in dogs are similar to those from limited observations in humans, similarities in metabolic profiles of these two species (i.e., xanthine oxidase) may explain the lack of interaction found in this trial (see below). Like other azoles, fluconazole is an inhibitor of multiple hepatic P-450 enzymes; it also appears to inhibit some non-P-450 enzymes, such as uridine diphosphate-glucurosyl transferase, which is responsible for the metabolism of ZDV (6,9,19). However, we found that the pharmacokinetics of ddI are not altered by fluconazole when both are given at commonly prescribed dosages.…”
Section: Discussioncontrasting
confidence: 47%
“…Fluconazole is well absorbed in the HIV population and is frequently prescribed for prophylaxis and treatment of fungal infections (6). However, fluconazole inhibits a number of hepatic P-450 enzymes that are responsible for the metabolism of many drugs, such as theophylline, phenytoin, cyclosporin, and rifabutin (9,16,21).…”
mentioning
confidence: 99%
“…One paper described the bioavailability (of a tablet formulation) and pharmacokinetics of fluconazole in people with AIDS (11). Single 100-mg intravenous and oral doses of fluconazole were administered.…”
mentioning
confidence: 99%